2014
DOI: 10.1016/j.bandl.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to lexical ambiguity: fMRI evidence for bilateral fronto-parietal involvement in language processing

Abstract: 187 wordsTotal number of words in the paper: 8,542 3 AbstractNumerous functional neuroimaging studies reported increased activity in the pars opercularis and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 62 publications
0
21
0
1
Order By: Relevance
“…Previous studies have found activation in right IPL related to mental manipulation of information and working memory tasks (Chochon, Cohen, Van De Moortele, & Dehaene, 1999; Klepousniotou, Gracco, & Pike, 2014; H. Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have found activation in right IPL related to mental manipulation of information and working memory tasks (Chochon, Cohen, Van De Moortele, & Dehaene, 1999; Klepousniotou, Gracco, & Pike, 2014; H. Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
“…These regions share connections with, and are linked to, language- and executive-related functions providing an adversity-related bridge between the brain, cognitive deficits, behavioral symptoms and persistent offending styles (Anda et al, 2006; Lansing et al, 2014; Piquero, 2001; Raine et al, 2005). The left pars opercularis, supramarginal gyrus, and lingual gyrus have been associated with language-related functions (auditory processing, language comprehension and production, word identification, recognition, and naming), social communication/cognition, and executive functioning (Badre et al, 2010; Frey et al, 2008; Kozlovskiy et al, 2014; Klepousniotou et al, 2013; Mechelli et al, 2000; Piquero, 2001; Raine et al, 2005; Skipper et al, 2007). LCPD boys' neuroanatomical correlations with adversity-related symptoms, coupled with smaller left hippocampal volumes in LCPD boys compared to controls, provide support for both verbal and visual-spatial difficulties reported in delinquent and non-delinquent maltreated populations (Lansing et al, 2014; Mothes et al, 2015; Raine et al, 2005), and suggest that difficulties are most common when there is increased executive demand (e.g., verbal working memory).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, "action syntax," or meaningful structured sequences of actions, may be related to structural processing in both music and language (Harding et al, 2011;Fazio et al, 2009;Fitch & Martins, 2014;Jackendoff, 2009;Sammler, Novembre, Koelsch, & Keller, 2013). Of course, cognitive control processes are not restricted to LIFG; it is clear that both left and right frontal mechanisms are involved in cognitive control (e.g., Aron, 2008;Gläscher et al, 2012), including in the sorts of revision-demanding situations discussed here (e.g., there is bilateral IFG involvement in the processing of lexical ambiguity; Klepousniotou, Gracco, & Pike, 2013). Because musical manipulations often involve bilateral frontal activation (see Figure 6, and Koelsch, 2011, for a review), musical processing may be particularly well suited to investigate the role of right frontal regions in complex cognition.…”
Section: Discussionmentioning
confidence: 99%